Understanding the Transfer of Training and the Barriers to Transfer: A Case Study in a Private Institution - Ng, Chiah Yee (2001)
The purpose of this study is to examine the transfer of training and its relationship with Trainees' Characteristic, Programme Design and Organization Support in skills transfer, using two evaluation methods: self-rating and end result measurement. The barriers of training transfer faced by programme participants were also studied. In addition, a comparison of mean differences was carried out on selfrating and end result evaluation method. A total of 52 middle managerial staffs both academic and non-academic from INTI COLLEGE, Nilai were selected using stratified random sampling techniques. These respondents participated in computer skill-training programmes, namely MS Word, MS Excel, MS PowerPoint and Internet conducted by the college in year 2000. Data was collected using self-administered survey questionnaire. Responses were analyzed using Statistical Package for Social Science (SPSS). Measures of Central Tendency, Standard Deviation and frequency were used for descriptive analysis while Person Product-moment Correlation Coefficient (r) was used to determine the relationship of the variables. Analysis of Paired-samples T-Test was used to determine the differences between the level of transfer of training using selfrating skill method and the end result measurement.